Perkembangan Industri Litik Penghuni Gua-Gua Di Jawa Timur - Indah Asikin Nurani (Balai Arkeologi Yogyakarta, 2004)
The influence of raw material is seen on the size of the tool. In the cave group on Mount Watang that uses rocks with a low level of silica (limestone), reliable artisan is demanded. This is because rock types are brittle and flaking them is difficult. Stone tool products in this group show a relatively large size due to the suboptimal flaking. Meanwhile, the stone tool products in the cave group in Sampung, Ponorogo is a microlithic. This is because the raw material has a relatively high level of silica (chert and chalcedony). The flaking techniques can be carried out optimally, resulting in small-sized stone tool products with micro trimming and flaking, both primary and secondary.